Increased frequency of positive antithyroid antibody in nodular goiter (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Nodular goiter is mostly a benign thyroid tumor. A change of frequency of nodular goiter in areas with sufficient iodine intake has been documented in several reports. However, contrary to common belief it may also be associated with autoimmunity is being observed recently by many investigators.Objectives: To observe association between thyroid autoimmunity and nodular goiter. Methods: This cross sectional study included two hundred cases and one hundred controls. Clinically suspected nodular thyroid patients were confirmed by USG. Selection of healthy control was done after exclusion of nodule clinically and by USG. Data were collected through a structured questionnaire.Results: Frequency of positive anti-thyroid antibodies was significantly higher in nodular goiter cases, when anti-TPO and anti-TG considered together (42.5% vs. 25.0%; ?2=8.792, p=0.003) as well as individually (anti-TPO: 37.0% vs. 20.0%; ?2=8.955, p=0.004 and anti-TG: 31.0% vs. 9.0%; ?2=17.861, p